Bone Mineral Density and Health-Related Physical Fitness of Middle-Aged Women - Jang, Hong-Young; Lee, Mihyun (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: The purpose of this study was to examine the relationship between the level of bone mineral density (BMD) and health-related physical fitness (HRPF) of middle-aged women. Methods: The participants in this study were composed of 47 menopausal women in their 45-55years, who were selected by convenience sampling. BMD was measured by using Dual Energy X-ray Absorptiometry. HRPF was measured by muscular strength, muscular endurance, cardiorespiratory endurance, flexibility, and body composition. The level of BMD was classified into two groups: T-score of –1 and above was sorted into the normal group, and T-score of –1 and below was sorted into the osteopenia group. The level of HRPF was also classified into two groups to analyze the odd ratio of osteopenia risk depending on the level of physical fitness. Findings: The group with normal BMD had significantly higher muscular strength, muscular endurance, and lean mass than the osteopenia group. Also, the group with the low level of HRPF had higher risk of osteopenia, which was 4 to 8 higher odds ratio of osteopenia than the group with a high physical fitness level. Applications: HRPF is critical for middle-aged women to reduce the risk of osteopenia and for promotion of health. Future studies are required to approach more comprehensively by examining the effects of amount of physical activities and eating habits on BMD.